Molecular and cellular events during blastocyst implantation in the receptive uterus: clues from mouse models - MATSUMOTO, Hiromichi (J Reprod Dev, 2017)
The success of implantation is an interactive process between the blastocyst and the uterus. Synchronized development of embryos with uterine differentiation to a receptive state is necessary to complete pregnancy. The period of uterine receptivity for implantation is limited and referred to as the “implantation window”, which is regulated by ovarian steroid hormones. Implantation process is complicated due to the many signaling molecules in the hierarchical mechanisms with the embryo-uterine dialogue. The mouse is widely used in animal research, and is uniquely suited for reproductive studies, i.e., having a large litter size and brief estrous cycles. This review first describes why the mouse is the preferred model for implantation studies, focusing on uterine morphology and physiological traits, and then highlights the knowledge on uterine receptivity and the hormonal regulation of blastocyst implantation in mice. Our recent study revealed that selective proteolysis in the activated blastocyst is associated with the completion of blastocyst implantation after embryo transfer. Furthermore, in the context of blastocyst implantation in the mouse, this review discusses the window of uterine receptivity, hormonal regulation, uterine vascular permeability and angiogenesis, the delayed-implantation mouse model, morphogens, adhesion molecules, crosslinker proteins, extracellular matrix, and matricellular proteins. A better understanding of uterine and blastocyst biology during the peri-implantation period should facilitate further development of reproductive technology.